Tropical fruits and vegetables extracts in food oxidative stability - Dos Santos, João Marcos [UNESP]; Monari Henck, Jenifer Mayara [UNESP]; Bonadio Bellucci, Elisa Rafaela [UNESP]; Bis-Souza, Camila Vespúcio [UNESP]; Da Silva Barretto, Andrea Carla [UNESP] (Elsevier, 2024)
The use of tropical fruit and vegetable extracts as natural antioxidants to improve the oxidative stability of food has been studied and the results are promising. The oxidation of food represents one of the great challenges to controlling and extending their shelf life, so antioxidants play a vital role in this balancing. The consumer recognizes these ingredients as natural and this has helped to explain this trend. The mechanism of action is associated with each antioxidant compound, which can be a flavonoid, a carotenoid, a terpene, hydroxycinnamic acid or vitamins from tropical fruits and vegetables. There are still many fruits and vegetables to be studied for use in different foods.
Keywords: Health food; Lipid oxidation; Natural antioxidants; Natural ingredients; Shelf life extension